Structural, Dielectric Permittivity and Optical Characteristics of Casting Poly Vinyl Alcohol/Calcium Nickel Aluminate Nanocomposite Films. Issue 10 (3rd July 2019) - H. M, Gayitri; Al-Gunaid, Murad; B S, Madhukar; Siddaramaiah, Basavarajaiah; A. P, Gnana Prakash
ABSTRACT: Triplex hybrid nanofiller (CaNiAl2 O5 ) have been synthesized by sol-gel method and its nanocomposite (NC) films were incorporated with poly vinyl alcohol (PVA). The scanning electron microscopy (SEM) was used to probe morphological behaviors and dispersion of CaNiAl2 O5 in PVA matrix. In order to probe the microstructure X-ray diffraction (XRD) and FTIR were performed on PVA/CaNiAl2 O5 NCs. Based on the results of both XRD and transmission electron microscopy (TEM), the average particle size of the CaNiAl2 O5 lies in the range 7–15 nm. The current (I) – voltage (V) behaviors were studied using LCR-meter at room temperature. The dc-conductivity increases with increasing in both CaNiAl2 O5 at different voltages. The dielectric constant exhibits higher values at lower frequency and increases with nanoparticle (NP) loading due to increase in polarization particles in polymer matrix. The ac conductivity tends to increase with increase frequency and NPs content. The cyclic voltammetric data indicate the NC with 8wt% NPs exhibit higher specific capacitance as compared with PVA. The optical constants of the NCs were evaluated from UV-Visible spectra. The band gap energies has a blue shift from 4.4 eV (PVA) to 2.8 eV (PVA/8wt% CaNiAl2 O5 ), whereas refractive index (RI) and the optical conductivity of NCs increased with an increasing in NPs content. GRAPHICAL ABSTRACT: